(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The research has identified the factors affecting the level of response to the job requirement of social workers when conducting counseling for families of children with autism in autism care and education centers. To achieve this goal, in this study we surveyed 89 social workers in Hanoi city. The results of the analysis of the multivariate linear regression model have shown that 6 factors have a significant impact on the level of response to the requirement of counseling skills when assisting autistic children’s families, including (i) passion for work, (ii) professional knowledge and practical experience, (iii) proactive activeness, (iv) training opportunities to improve qualifications, (v) employment incentives, (vi) job requirements. The results showed that the passion for the job was most appreciated. On this basis, the study offers several meaningful solutions to improve the job response level of social workers when conducting counseling for autistic children’s families.